Implementation of Learning Prayer for Mental Retardation - Krismajoli Dwi Pamuladsih; Sunardi Sunardi; Joko Yuwono (International Inclusion Development and Cooperation, 2022)
This study aims to: (1) find out the implementation of Islamic Religious Education learning materials for movement and prayer readings for mentally retarded students, (2) find out learning resources and media, learning methods, and evaluations carried out by teachers. The research method used in this research is descriptive qualitative. The results showed that the ability to move and read prayers for mentally retarded children was still low, this was because: (1) learning resources and media from the three schools studied were still using conventional media, (2) learning methods were still using the lecture method which was teacher center, (3) notes from the teacher regarding the low prayer skills of mentally retarded children due to: the loss of routines or good habits applied at school during the implementation of distance learning, the use of media that is still very simple, and the absence of continuous prayer learning to be applied at home.